Effect of Pulsed Electric Field-Assisted Extraction on Recovery of Sulforaphane from Broccoli Florets - Mahn-Osses, A (John Wiley and Sons Inc, 2022)
Sulforaphane (SFN) is an isothiocyanate occurring in broccoli, with exceptional health-beneficial properties, such as anticancer, anti-inflammatory, and anti-hypertensive effects. Processes to maximize SFN content in broccoli developed until now are expensive and SFN bioavailability in the vegetable is not optimal. To increase SFN extraction yield from broccoli florets, it was proposed to complement traditional solvent extraction with pulsed electric field (PEF) as tissue disruption method enabling the reduction of mass transfer resistance in vegetable matrices. Tissue disruption methods enhance the performance of this process because it reduces mass transfer resistance. PEF is an innovative technology recently introduced in the food industry. We studied the effect of electric field strength (10 and 15 kV/cm) and time of exposure to the PEF treatment (30, 90, and 150 s) on the recovery of SFN from broccoli florets, using a statistical factorial design. Electric field strength and exposure time significantly affected SFN recovery in a positive way. PEFs increase SFN recovery by more than 50% compared to traditional extraction. This result was achieved at 150 s exposure to PEF and 10 kV/cm. Practical Applications: The use of pulsed electric fields significantly improved sulforaphane recovery from broccoli in comparison with traditional extraction methods. Even though in this work the raw material was commercial broccoli heads, it is most likely that the results obtained here can be replicated using low-value raw material, such as broccoli heads that do not meet commercial standards or crop discards. Accordingly, PEF technology constitutes an option for valorization of Brassicaceae agroindustry discards. © 2021 Wiley Periodicals LLC.